Elevated D-Dimers and C-Reactive Protein Levels as a Risk Factor for Development of Thrombotic Events in Type 2 Diabetes Mellitus (Medical Forum Monthly, 2024)
Objective: To study the levels of C-Reactive Protein and D-dimers in diabetic patients.Study Design: Descriptive study.Place and Duration of Study: This study was conducted at the Departments of Medicine and Pathology at Bacha Khan Medical College and Teaching Hospital Mardan from January to June 2016.Materials and Methods: The study included a total of 150 patients. Out of these 150 patients, d-dimer levels were measured in 50 patients and CRP levels in the other 50.Remaining 50 patients were included in the control group. In control group, which comprised of non diabetic patients, d-dimer and CRP levels were measured in all 50 patients.Results: CRP was elevated in 22 out of 50 patients (44%) and d-dimers were elevated in 32 out of 50 patients (64%). Five out of 50 patients had D-dimers levels in the range of 250-500ng/ml. 15 out of 50 patients had d-dimer levels in the range of 500-1000ng/ml and 10 out of 50 patients had d-dimers levels in the range of 1000-2000ng/ml. The study showed that both CRP and d-dimer levels were elevated in type 2 diabetic patient as compared to control group in which only 3 out of 50 patients had elevated d-dimer and 4 out of 50 had elevated CRP.P-value for CRP was less than 0.0035 and for d-dimer sit was less than 0.0032.Conclusion: The study concluded that diabetic patients are associated with significantly elevated level of CRP and d-dimer level. CRP is an inflammatory marker and d-dimer is hemostatic marker.Elevated levels identify patients who are predisposed to thrombotic events and thus useful to identify at risk patients. Early management in these patients reduce thrombotic complications.